Analysis of Student Satisfaction with Services Using the Service Quality (ServQual) Method - Dzikri, M.; Napitupulu, Lilis Suryani; Nasution, Donni (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2024)
This study aims to analyze the level of student satisfaction with services at SMK Swasta Perguruan Mabar, a private vocational school in North Sumatra that offers education in Accounting. The quality of school services, which includes learning services, management, facilities, and other aspects, is the main focus in an effort to increase student satisfaction and improve the quality of education. The Service Quality (ServQual) method is used in this study to evaluate service quality based on five dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The results of the analysis show that the level of student satisfaction is 3.482, which is categorized as good. This finding indicates that the ServQual method is effective in measuring student satisfaction by using expected value as the main benchmark, thus providing more accurate and objective results in assessing student satisfaction with the services provided. This research is expected to provide insight for school management to further improve the quality of services provided to students. Keywords: Students, Satisfaction, School, Service Quality